Pawisik Nabe Dalam Upacara Diksa di Griya Agung Bangkasa - Wardana, I Ketut; Saitya, Ida Bagus Subrahmaniam; Ambarnuari, Mery (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Pandita as a clergy has a position and authority in the religious life of Hindu society. The aguron-guron system is an educational system developed by Hinduism to teach knowledge and skills in the religious field. The system is still very relevant to pass on spiritual knowledge in the process of giving birth to a pandita/sulinggih. Research related to pewisik nabe in the diksa kepurusan ceremony of Griya Agung Bongkasa because this griya is one of the old griyas with a long lineage and is committed to developing the aguron-guron system. There are three problems discussed in this study, namely related to the form of the aguro-guron system of Griya Bongkasa, the function of pawisik Nabe in the diksa ceremony at Griya Agung Bangkasa, and the meaning of Hindu theology in pawisik Nabe in the diksa ceremony at Griya Agung Bangkasa. This qualitative research with a theological approach uses Religion theory, structural functionalism theory and symbolic interactionism to dissect the problem so that the data can be presented in a qualitative description. The aguron-guron system in Griya Agung Bangkasa has educational, religious, and social functions. And the last is related to the implications of the aguron-guron system in Griya Agung Bangkasa which raises educational, theological, and sociological implications both internally and externally. This aguron-guron system is special because of the Nabe pawisik at the diksa ceremony at Griya Agung Bangkasa as an effort to improve the quality of aguron-guron education carried out. The exclusive aguron-guron system is the best choice in providing spiritual education. This system can enrich the education system so as to create a holistic education.